Pengaruh Sektor Transportasi Terhadap Investasi Asing dan Kualitas Udara di Indonesia (Wilayah Pulau Jawa) - Aflediani Tokan, Megapuspa Marieta; Fitriani, Rizki (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
Indonesia is one of the developing countries that continues to develop in various sectors. In order for these activities to run, a very large budget is needed. The need for a large budget will directly or indirectly impact economic development in Indonesia. To overcome this, the government is trying to attract foreign investors to invest in Indonesia. Thus, economic activity in Indonesia can continue and meet the needs of the community. Although it has a positive effect, it also indirectly has a negative effect on air quality. This is because economic activity is supported by the transportation sector. Increased transportation activity will reduce air quality by increasing the number of vehicles with smoke and increasing the concentration of carbon dioxide and carbon monoxide in the air. This study aims to determine the effect of foreign investment and economic activity on air quality in Indonesia. The method used in this research is a literature study. Literature study is carried out by searching for articles from journals related to the topic under study. The results of the study show that an increase in foreign investment in Indonesia every period will increase economic activity and reduce air quality in Indonesia.